Dual Effectiveness of Freezing-Thawing and Sulfate Attack on High-Volume Slag-Incorporated ECC - Ozbay, Erdogan; Karahan, Okan; Lachemi, Mohamed; Hossain, Khandaker M. A.; Atis, Cengiz Duran (Elsevier Sci Ltd, 2013)
This study investigated the dual effect of freeze-thaw cycles with sodium sulfate solution on the performance of non-air-entrained Engineering Cementitious Composites (ECCs) with high volumes of slag. ECC specimens containing three different levels of slag content as a replacement for cement (55%, 69% and 81% by weight of total cementitious material) were exposed to aggressive sodium sulfate solution under freezing-thawing cycles. The load-deflection response associated with ultimate mid-span deflection and flexural strength/stiffness was determined, along with crack development behavior. For comparison purposes, the freezing-thawing resistance (in water) of control ECC specimens was also evaluated. Modified point count method air-void parameters, compressive strength, porosity, water absorption and sorptivity tests were also conducted on the virgin ECC specimens (those not exposed to freezing-thawing cycles in water or aggressive sodium sulfate solution). The test results for the virgin specimens revealed that increased slag content (S/PC) improved the ductility, hardened air content, water absorption, porosity and sorptivity of ECC, while marginally decreasing the compressive and flexural strengths. Freeze-thaw cycles in water or sodium sulfate solution showed that the ductility of ECC specimens decreased remarkably, irrespective of slag content and applied freezing-thawing process. Reduction in mass loss was at minimal levels and no significant behavior change was monitored between the specimens undergoing freeze-thaw cycling in water and the aggressive sodium sulfate solution. Moreover, the decrease in flexural stiffness was more evident than the reduction of the flexural strength for all ECC mixtures. Crown Copyright (c) 2012 Published by Elsevier Ltd. All rights reserved.
Keywords: Fibers; Cure Behavior; Environmental Degradation; Mechanical Testing; B. Environmental Degradation; A. Fibers; B. Cure Behavior; D. Mechanical Testing